EFFECTS OF La2O3 AND Bi2O3 ADDITIONS ON THE MICROWAVE DIELECTRIC AND ANTENNA PROPERTIES OF SrBi2Nb2O9 CERAMIC MATRIX - Abreu, Roterdan Fernandes; Silva, Felipe Rodrigues; SATURNO, SAMUEL OLIVEIRA; COLARES, DIEGO DA MOTA; ABREU, TALLISON OLIVEIRA; do Nascimento, João Paulo Costa; Sancho Oliveira, Emmanuelle de Oliveira; Sales, Juscelino Chaves; Gouveia, Daniel Xavier; Sombra, Antônio Sérgio Bezerra (Journal of Mechatronics Engineering, 2021)
This work presents a comparison between the dielectric properties of the SrBi2Nb2O9 (SBN)ceramic matrix and the individual additions of Bi2O3and La2O3, suggesting the material that would be most suitable for microwave applications. The SBN sample was synthesized by solid-state reaction, and the X-ray diffraction method (XRD) was used for the structural characterization of the materials analyzed in this study. The thermal stability of the samples was measured experimentally by studying the temperature coefficient of resonant frequency (τf) the results confirm that the individual additions of 15wt% of Bi2O3or La2O3improved the thermostability of the composites. The Hakki-Coleman method was used to obtain the dielectric properties in the microwave range, and it is possible to observe that the dielectric permittivity of the composites increased, while their loss tangents decreased. The numerical simulation demonstrated the functioning of the materials as dielectric resonating antennas (DRA), with a reflection coefficient below -10 dB in all samples.